Management of Private-aided Higher Education in Karnataka, India - James Tooley (Educational Management Administration Leadership 2005; 33; 465, 2005)
The Grant-in-Aid (GIA) higher education sector in Karnataka, India, is examined as an example of a well-established public-private partnership (PPP). Interviews with senior officials in the Government of Karnataka, and in two contrasting Regions, centred around Gulbarga and Mysore, together with visits to GIA and private-unaided (PUA) colleges were undertaken. The study showed how devolved financial management led to problems of potential misuse of subsidy and to substantial inefficiencies. The regulation of the sector is explored, revealing inconsistencies between theory and practice, and unforeseen consequences in terms of a lack of teacher accountability and low investment. Considerations concerning equity are outlined, noting how GIA proponents who argued that it was effective in helping the poor might not be on strong grounds. Finally, implications are discussed for PPPs more generally.